A facile and scalable process to synthesize flexible lithium ion conductive glass-ceramic fibers. Issue 8 (31st January 2019) - He, Kun; Xie, Pu; Zu, Chengkui; Wang, Yanhang; Li, Baoying; Han, Bin; Rong, Min Zhi; Zhang, Ming Qiu
Abstract : A flexible lithium ion conductive Li1.5 Al0.5 Ge1.5 (PO4 )3 glass-ceramic fiber was prepared by melt-spun method. Abstract : Solid-state electrolytes have emerged as a promising alternative to existing liquid electrolytes for next-generation flexible Li metal batteries with enhanced safety and stability. Nevertheless, the brittleness and inferior room temperature conductivity are major obstacles for practical applications. Herein, for the first time, we have fabricated a flexible lithium ion conductive glass-ceramic fiber by using a melt-spun homogeneous NASICON-type structured Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) glass melt and annealed at 825 °C. The annealed samples exhibited a higher lithium ion conductivity than the air-quenched sample due to the presence of a well-crystallized crystal grain in the annealed sample. Meanwhile, the ionic conductivity has shown an inverse relationship with the diameter of annealed LAGP glass-ceramic fibers. The results revealed that the annealed glass-ceramic fiber, with a diameter of 10 μm, resulted in lithium ion conductivity of 8.8 × 10 3 S cm −1 at room temperature.